Neoadjuvant camrelizumab and chemotherapy in patients with resectable stage IIIA squamous non-small-cell lung cancer: Clinical experience of three cases - Li, Xin; Xia, Chunqiu; Liu, Minghui; Liu, Jinghao; Dong, Ming; Zhao, Honglin; Xu, Song; Wang, Dan; Wei, Sen; Song, Zuoqing; Chen, Gang; Liu, Hongyu; et al. (Frontiers in Oncology, 2022)
Neoadjuvant immunochemotherapy has attracted much attention as a treatment for locally advanced non-small-cell lung cancer. However, there is scarce evidence of the safety and efficacy of camrelizumab as neoadjuvant in lung cancer. Here, we present three patients who were diagnosed as IIIA squamous non-small-cell lung cancer from September to December in 2020, and received two cycles neoadjuvant camrelizumab plus nab-paclitaxel and nedaplatin, then followed by surgical resection. All three patients had reduction in the tumor size on CT image and not delayed planned surgery. We did not observe grade 3 or 4 adverse events. Two of the three patients achieved a major pathological response (MPR), including one complete tumor regression of the primary lung tumor. Multiplex fluorescent immunohistochemistry revealed that CD8+ T cells, FoxP3+ regulatory T cells, and PD-L1 expression on immune cells in the surgical specimen were much higher than in the pretreatment biopsy sample in patients with MPR. This was not observed in the patient without MPR. Camrelizumab plus chemotherapy could potentially be a neoadjuvant regimen for resectable IIIA squamous non-small-cell lung cancer, with high MPR proportion and did not compromise surgical procedure. Our findings should be validated in a future randomized clinical trial.